2019
DOI: 10.18267/j.pep.705
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Harmonization on the Implicit Tax Rate of Consumption

Abstract: This paper brings to the foreground an indicator rather less used in specialized studies-the implicit tax rate of consumption-as an effective tax rate of consumption. In an empirical analysis, we try to analyse the impact of the main determinants on the implicit tax rate of consumption. The analysis is based on the panel technique in order to show the impact of tax harmonization on consumer taxation at EU27, EU15 and NMS12 levels, testing three hypotheses: (1) the implicit tax rate of consumption is directly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Accordingly, Chan and Ramly (2018) highlight that value-added tax is a powerful tool to increase tax revenues in developing economies. Feher et al (2019) emphasize the importance of consumption taxes, and these tax forms are identified as the valuable fiscal policy instruments for European Union member states. Auray et al (2016) indicate that consumption tax offers the greatest long-term potential revenue improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, Chan and Ramly (2018) highlight that value-added tax is a powerful tool to increase tax revenues in developing economies. Feher et al (2019) emphasize the importance of consumption taxes, and these tax forms are identified as the valuable fiscal policy instruments for European Union member states. Auray et al (2016) indicate that consumption tax offers the greatest long-term potential revenue improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Collectively, these factors can be seen as drivers of tax evasion. According to previous researchers, individuals experiencing personal financial constraints are more prone to engage in tax evasion than individuals who are not in this financial situation (Engida & Baisa, 2014;Feher et al, 2019).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Milasi and Waldmann (2017) argue that raising top marginal tax rates which are below their growth maximum has the greatest positive effect on growth when the related additional revenues are used to finance public expenditures and reduce budget deficits. Feher et al (2019) argue that value added tax is the most effective tax during the crisis to reduce budget deficits.…”
Section: Introductionmentioning
confidence: 99%